The Combined Effect of Trachyspermum Supplementation and Jump Rope Exercise on Abdominal Obesity and Cardiovascular Risk Factors in 10-15 Year-Old Boys - Majid Mirhosseini; Ali Younesian; Hamid Namavar; Shahrbanoo Goli (Iranian Journal of Diabetes and Obesity, 2025)
Objective: Childhood and adolescent overweight can lead to metabolic syndrome in adulthood. This study aimed to evaluate the effect of Trachyspermum supplement and jump rope exercise on abdominal obesity and cardiovascular risk factors in obese boys aged 10-15. Materials and Methods: In this clinical trial, 60 obese boys with waist circumference above the 90th percentile were selected using cluster random sampling from schools in Shahroud. The participants were randomly assigned to four groups: (1) supplement + exercise, (2) exercise only, (3) supplement only, and (4) control. The intervention lasted eight weeks. The Jump rope training was done 5 days per week for 30 minutes, with progressive intensity, based on Sung Kim’s protocol. Supplement groups received 3g/day of Trachyspermum powder after breakfast. Measurements included waist/abdominal circumference, weight, and blood tests for Low Density Lipoprotein (LDL), High Density Lipoprotein HDL, triglycerides, total cholesterol, and fasting blood sugar before and after the intervention. Statistical analyses included Shapiro-Wilk, Kolmogorov-Smirnov for normality, chi-square, ANOVA, and post hoc tests using SPSS, with significance at P< 0.05. Results: The combination of Trachyspermum and the jump rope exercise significantly improved abdominal obesity (P< 0.011), LDL (P< 0.005), HDL (P< 0.029), triglycerides (P< 0.005), and fasting blood sugar (P< 0.001), compared to control and exercise-only groups. No significant change was found in total cholesterol (P< 0.343). Conclusion: The combination of Trachyspermum and jump rope training had beneficial effects on obesity and cardiovascular risk factors in adolescents, suggesting its use as a non-pharmacological and complementary treatment for adolescent obesity.